Cultural and Social Capitals for Recovering from Covid-19 Pandemic in Lebakmuncang Tourism Village - Farida Ayu Brilyanti; Tri Joko Purwanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Covid-19 pandemic has had an impact on reducing tourist visit numbers and agricultural products sales in Lebakmuncang Tourism Village, Bandung Regency, West Java. This study aims to identify the cultural capital and social capital that owned by Lebakmuncang Tourism Village people; to find the undeveloped potential in Lebakmuncang Tourism Village management and development; and provide recommendations for optimizing the Lebakmuncang Tourism Village management from Social Capital and Cultural Capital aspects. This study uses a qualitative approach using primary and secondary data. Based on the results, Lebakmuncang Tourism Village people has good cultural and social capital to support the Lebakmuncang Tourism Village development after Covid-19 pandemic.